2016
DOI: 10.3390/su8050412
|View full text |Cite
|
Sign up to set email alerts
|

Scottish Passive House: Insights into Environmental Conditions in Monitored Passive Houses

Abstract: Climate change and sustainability legislation in recent years has led to significant changes in construction approaches in the UK housing sector. This has resulted in the adoption of new building typologies, including the German Passivhaus (Passive House) standard. This standard aims to improve occupant comfort and energy efficiency, potentially changing the ways in which homes operate and how occupants interact with them. With increasing construction of low energy dwellings, there is an emerging gap in knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Similar issues have been reported also for the colder climates of Scotland [28] and Estonia [29], as well as for the continental one of Slovenia [30] and Romania [31].…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…Similar issues have been reported also for the colder climates of Scotland [28] and Estonia [29], as well as for the continental one of Slovenia [30] and Romania [31].…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…Surveys of a modest sample of Passive House buildings were carried out in-situ [49] and supported the conclusion of research identified earlier that the Passive House standard was robust and gave predictable savings. Research has also shown however that some Passive House dwellings have exhibited some more marginal outcomes [50] and that there is some lack of information in published sources about performance. The study examined five dwellings in Scotland and indicated concerns in the areas of indoor air quality, comfort and occupant health.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…The identified literature includes four studies that reported from virtual simulations [ 47 , 51 , 52 , 66 ], one study based on occupant perception of IAQ, three used low-cost monitors [ 41 , 44 , 56 ], twenty-nine included physical IAQ measurements [ 41 , 42 , 43 , 44 , 45 , 48 , 50 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 65 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] and fourteen studies assessed IAQ through both physical measurements and occupant perceptions [ 41 , 42 , 43 , 55 , 56 , 58 , 59 , 64 , 65 , 66 , 72 , 73 , 76 ]. Only thirteen of these measured IAQ metrics other than CO 2 [ 41 ,…”
Section: Resultsmentioning
confidence: 99%
“…One of the biggest challenges to compare IAQ between different studies is the lack of homogeneous methods to report IAQ. Some studies do not describe the energy performance (four studies: [55,56,72,77]) or describe IAQ absolute values (fifteen studies: [43,44,46,50,51,57,58,61,[65][66][67][68][69][70]75]) and express relative levels (i.e., percentage of time above or below particular thresholds)-which also happen to vary from one study to another, in addition to the differences of monitored periods. Additionally, the timeframe on which studies are conducted varies.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation